The change in education in the XXI century: Echoes from sciences in contemporary early childhood education - Cristina Cruz Mateus; Dulce Noronha Sousa (Escola Superior de Educação de Paula Frassinetti, 2016)
Like any science education, in its more general conception, demands to agree principles, on the one hand, guiding a pedagogy that aims at the proactive child and conscious thinkers, on the other hand, buoyed by a culture of values that aim at a solidarity intergenerational citizenship, where there is no child's world but this one belongs to him by right. These principles are fundamental, in an apparent paradox, when we report to the knowledge society in vertiginous change. It is important, therefore, to conceptualize the issue of "society change versus educational change" (today's children, technological, parents, without educational references, educators, updated reflection, schools, with educational principles). The support of change is rebuilt in an educational proposal in which echoes of sciences such as philosophy, sociology, psychology and neuroscience are felt. Keywords: Echoes; Science, Education; Change; Thinkers